Mechanical characterization of Carbon Fibre and Graphene Oxide Reinforced Epoxy Hybrid Composite - Sakib, Md. Nazmus; Asif Iqbal, AKM; Muhammad Nuruzzaman, Dewan (Springer Singapore, 2021)
In this study, graphene oxide (GO) and carbon fibre (CF) reinforced epoxy hybrid composite has been fabricated by vacuum resin infusion method and the influence of GO reinforcement on the tensile and flexural properties has been investigated. Three different concentration of GO 0.2, 0.4 and 0.6 wt% were used to develop hybrid composite samples. The results show that both the tensile and flexural strength increase once GO is added to the epoxy-CF composite. Among the three different concentration of GO, 0.4 wt% GO reinforced hybrid composite exhibits superior mechanical properties and can be considered as the optimum value in augmenting the mechanical performance of the hybrid composite.